Implementasi Peningkatan dalam Aktivitas Rantai Nilai Global oleh UKM Kopi Indonesia: Hasil Studi Empiris - Alidyan Kresnawati, Megahnanda; Wardhani, Baiq Lekar Sinayang Wahyu; Dugis, Vinsensio M. A. (Parahyangan Center for International Studies, 2025)
This study discusses the implementation of improvement strategies in the global value chain (GVC) for coffee SMEs in Indonesia. With the background of Indonesia's position as a major coffee producer in the world, this study explores the challenges faced by SMEs in achieving maximum added value, broad market access, and effective governance. The research method uses a qualitative descriptive approach through literature analysis, secondary data and primary data related to the coffee value chain and its improvement strategies. The results show that value-added improvement strategies can be achieved through product, process, and function innovation, as well as product differentiation. Certification such as Geographical Indications helps increase sales value, although benefits for farmers are still limited. Increasing market access involves vertical and horizontal collaboration for diversification and development of marketing networks, including participation in international exhibitions. The role of the government is very important through the development of infrastructure, regulations, and certification support, but needs to be strengthened to reduce the imbalance in the distribution of added value. In conclusion, partnerships involving the private sector, government, and NGOs are key to encouraging the sustainability of coffee SMEs in the GVC. Recommendations include strengthening governance, increasing farmer capacity, and collaboration strategies to expand export markets and increase the competitiveness of Indonesian coffee in the global market. Keywords: Upgrading, Global Value Chain (GVC), Indonesian Coffee SMEs.